Contemporary State of Antibiotic Resistance in Opportunistic Pathogens and the Extent of Antibiotic Use in the Third-Level Federal Obstetric Hospital - D. M. Serdyukova; N. E. Shabanova; L. A. Lyubasovskaya; A. V. Nikolaeva; R. G. Shmakov; A. V. Skorobogatiy; T. V. Priputnevich (Антибиотики и Химиотерапия)
An increase in the frequency of antibiotic consumption, especially their irrational use as empirical therapy, led to an increase in the resistance of microorganisms and caused a significant decrease in the effectiveness of antibiotic treatment. In the course of the study, a retrospective pharmacoepidemiologic analysis of the consumption of antimicrobial agents and microbiological monitoring were conducted in obstetric departments of the National Medical Research Center for Obstetrics, Gynecology and Perinatology named after Academician V. I. Kulakov for the 2014-2018. A comparative analysis of antibiotic consumption indicators was carried out before and after the implementation of Risk Stratification Approach (patients with infection are stratified according to the risk of poly-resistant pathogens). Standardized ATC/DDD methodology was used to assess the dynamics of antibiotic consumption. Antibiotic levels were assessed by the rate of DDD/100 bed days, with total DDD accepted by WHO. As a result of pharma-coepidemiologic analysis and microbiological monitoring, the main vectors of empirical antibiotic therapy in an obstetric hospital of level 3 federal significance were determined. The widespread use of protected aminopenicillins and the tendency to increase their consumption can lead to a decrease in the sensitivity of enterobacteria - the main opportunistic pathogens in obstetrics and gynecology - to them. The study showed that the sensitivity of E.coli to beta-lactam antibiotics remains quite high. Nevertheless, increasing consumption of cephalosporins can provoke «parallel damage» and, as a result, increase the level of antibiotic resistance in medical institutions. The sensitivity of Enterobacterial strains to fluoroquinolones remains at a high level, so these drugs should be classified as second-line antibiotics and used in case if the initial treatment of postpartum infectious complications proves to be ineffective. Nevertheless, it is advisable to use protected aminopenicillins for the purpose of perioperative prophylaxis and initial therapy. The study also demonstrated that the introduction of stratification of hospitalized patients with infection reduced the consumption of antibiotics, taking into account the risk of multiresistant pathogens release in the Center. Using the DDD methodology, the authors were able to determine the rational volumes of antibiotic consumption in obstetric departments: not exceeding 810 DDD/100 bed days for Department of Physiology and not more than 15-20 DDD/100 bed days for Department of Pregnancy Pathology. Reliable data on antimicrobial consumption and microbiological monitoring should form a basis for national and local policies devised to reduce the resistance of microorganisms to antibiotics.